Serological detection and molecular characterization of piroplasmids in equids in Brazil - Vieira, Maria Isabel Botelho; Costa, Márcio Machado; de Oliveira, Mateus Tonial; Gonçalves, Luiz Ricardo [UNESP]; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP] (Elsevier, 2018)
Equine piroplasmosis is a disease caused by the hemoparasites Babesia caballi and Theileria equi and is considered to be the most important parasitic infection affecting Equidae. The objective of the present study was to carry out an epidemiological molecular and serological survey for the presence of these two protozoal organisms in equids from the northwestern region of the State of Rio Grande do Sul (RS), south Brazil. For this purpose, blood samples were collected from 90 equids in the city of Passo Fundo, RS, Brazil. Those were animals used for sport activities, outdoor recreational riding, and work including cattle herding and mounted patrol. Anti-T. equi and anti-B. caballi IgG antibodies were detected in the sera of those animals by commercial ELISA kits. The molecular diagnosis of equine piroplasmosis due to T. equi or B. caballi (or both) consisted in the amplification of the 18S rRNA gene by nested PCR followed by sequencing of the amplified PCR product and sequence comparison and phylogenetic analysis of the isolates; 17 (18.9%) and 5 (5.55%) out of the 90 serum samples tested in this study were positive for T. equi and B. caballi, respectively. Piroplasmid 18S rRNA gene fragments were detected by PCR in 24.4% (22/90) of the samples analysed and shared 99–100% identity with sequences of T. equi by BLASTn. Samples for the phylogenetic analysis were divided into 2 groups. In group A, there was close phylogenetic relationship between 4 sequences and sequences previously reported along the US-Mexico border, in South Africa, and in Brazil. There was a phylogenetic proximity between 5 samples from group B and samples tested by other authors in the US and Spain. Variation of the 18S rRNA gene allowed the identification of 9 new T. equi genotypes in the geographical region studied.
Keywords: 18S rRNA gene; Babesia caballi; Brazil; Equine piroplasmosis; Rio Grande do Sul; Theileria equi